Personalmarketing im Rettungswesen: Eine Analyse des Employer Brandings in Rettungsdiensten der Deutschschweiz - Felix Brinkmann (Tectum, 2024)
– To prevent experienced rescuers from leaving the service and losing their expertise and routine, recruitment marketing and the employer brand should be improved and expanded. Both are becoming increasingly important in times of skills shortages. The author empirically examines the needs and expectations of specialised rescue personnel and compares them with the assessments of rescue service managers. He draws a representative picture of the current situation in the rescue services of German-speaking Switzerland, from which forward-looking conclusions and recommendations can be derived.
Keywords: 650; Employer Value Proposition